Preparation and characterization on carrageenan derivatives as solid biopolymer electrolyte - Rafiq Izzuddin, Radzali (2017)
Bio-polymer are the renewable resources which easily can degraded by natural processes. Since this material was abandoned in earth, this present research was conducted in order to produce solid form biopolymer electrolyte. The solid biopolymer electrolyte which produced by using kappa carrageenan doped with ammonium nitrate was successfully prepared. The objective of this research were to prepare the solid biopolymer electrolyte based on kappa carrageenan doped NH4NO3 complexes, to identify the transport properties and ionic conductivity of kappa carrageenan doped with NH4NO3. In this research content 3 phase which is preparation phase, characterization phase and lastly analysis phase. The prepared sample were characterized by using Electrical Impedance Spectroscopy (EIS), Fourier Transform Infrared Spectroscopy (FTIR) and Transference Measurement Number (TNM). From EIS result, the highest ionic conductivity was found to achieve for sample with 40 wt. % at 9.64×10-4 Scm−1. The analysis of EIS including the dielectric study was carried out in order to investigate the behavior such as dielectric loss, and dielectric constant. Moreover, the result FTIR is show the shifted peak of functional group which indicate the complexation has occurred between kappa carrageenan and ammonium nitrate. The FTIR deconvolution study also need to study on FTIR analysis. The TNM shown that the ionic conducting species of solid biopolymer electrolytes due to the cation.